2019
DOI: 10.1111/bjet.12834
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subjective norms on preservice and in‐service teachers’ behavioural intentions to use technology: A multigroup multimodel study

Abstract: Technology acceptance model (TAM) is one of the models that is used to explain the acceptance and use of technology with user perceptions and attitudes. Some researchers argued that TAM should include external variables, such as subjective norms, to improve our understanding of the effect of social impact on technology acceptance. The purpose of this study was to investigate the effect of subjective norms on preservice and in‐service teachers’ perceptions, attitudes and behavioural intention to use technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 58 publications
7
38
1
7
Order By: Relevance
“…All measurement items used in this study were adapted from published sources (Bai et al, 2019 ; Kao & Tsai, 2009 ; Teo et al, 2016 ; Ursavaş et al, 2019 ; Wang & Wang, 2009 ). Moreover, in order to design the questionnaire content during the coronavirus pandemic, two experts in the field of online teaching and learning were consulted for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All measurement items used in this study were adapted from published sources (Bai et al, 2019 ; Kao & Tsai, 2009 ; Teo et al, 2016 ; Ursavaş et al, 2019 ; Wang & Wang, 2009 ). Moreover, in order to design the questionnaire content during the coronavirus pandemic, two experts in the field of online teaching and learning were consulted for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Bao’s research echoes the following view that the teacher is the key factor in the successful implementation of technology in the classroom (Chen et al, 2009 ; Sánchez-Prieto et al, 2017 ). Recent research on educational technology also found that teachers’ beliefs about the use of technology determine their intentions to adopt technology-enhanced instructional activities and teaching practices (Bai et al, 2019 ; Ursavaş et al, 2019 ). Therefore, this study takes university teachers as the research object to examine the factors that affect their intention to use a mobile teaching platform.…”
Section: Introductionmentioning
confidence: 99%
“…Infrastructure includes the internet, communication devices, and computer labs. [54] and [55] suggested that infrastructure as "internet/computer access, electricity, and systems efficiency plus availability" is a common thread and should be addressed to guarantee the success of ICT-supported learning. The quality of the internet connection, which comprises internet reliability and speed, is considered a significant factor in the infrastructure that can provide a suitable medium for using SNTs in classes, labs, and other areas in universities [41].…”
Section: B Infrastructure and Social Network Toolsmentioning
confidence: 99%
“…However, few studies have examined patrons' perceptions (including TTF and technology acceptance) after using the system. Therefore, attention must be paid to university library patrons' TTF when investigating their use of mobile libraries (Ursavas et al, 2019).…”
Section: Task-technology Fitmentioning
confidence: 99%